Sexing of murine and bovine embryos by developmental high-titer arrest induced by H-Y antisera - Ramalho, MFPDT; Garcia, J. M.; Esper, C. R.; Vantini, R.; Alves, BCA; Almeida, I. L.; de Lima, VFMH; Moreira, C. A. (Elsevier B.V., 2004)
Murine and bovine embryos at the late morula stage were cultured in medium containing high-titer rat H-Y antisera. After 12 h of incubation, embryos blocked at the late morulae stage were classified as males and those at the blastocyst stage were classified as females. Sexing of murine embryos by PCR and cytogenetics revealed that 83% of the embryos classified as males and 82% of those classified as females had their sex correctly predicted (P < 0.05). Bovine embryos were transferred to recipient females. Pregnancy rates were 71.4% (10/14) for embryos classified as males and 68.8% (11/16) for embryos classified as females. The sex was correctly predicted for 80% (8/10) of the embryos classified as males and for 81.8% (9/11) of those classified as females (overall accuracy, 80.9%, P < 0.05). Therefore, the induction of developmental arrest by high-titer male-specific antisera was an efficient strategy for non-invasive embryo sexing. The procedure was straightforward and has considerable commercial potential for sexing bovine embryos. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: embryo sexing; developmental arrest; H-Y antisera